2014
DOI: 10.3389/fnagi.2014.00013
|View full text |Cite
|
Sign up to set email alerts
|

Aged rats are hypo-responsive to acute restraint: implications for psychosocial stress in aging

Abstract: Cognitive processes associated with prefrontal cortex and hippocampus decline with age and are vulnerable to disruption by stress. The stress/stress hormone/allostatic load hypotheses of brain aging posit that brain aging, at least in part, is the manifestation of life-long stress exposure. In addition, as humans age, there is a profound increase in the incidence of new onset stressors, many of which are psychosocial (e.g., loss of job, death of spouse, social isolation), and aged humans are well-understood to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
1
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 185 publications
(233 reference statements)
2
37
1
6
Order By: Relevance
“…In contrast to the clear effects observed in young adults (for a review see Wolf, 2009), previous studies in older animals and humans did not show any acute effects on spatial memory (Buechel et al, 2014), learning, short-term declarative or non-declarative memory (Porter et al, 2002), or long-term memory retrieval of pictures, words and stories (Pulopulos et al, 2013). However, we have observed a specific effect of stress-induced cortisol response on retroactive interference (i.e.…”
Section: Discussioncontrasting
confidence: 97%
“…In contrast to the clear effects observed in young adults (for a review see Wolf, 2009), previous studies in older animals and humans did not show any acute effects on spatial memory (Buechel et al, 2014), learning, short-term declarative or non-declarative memory (Porter et al, 2002), or long-term memory retrieval of pictures, words and stories (Pulopulos et al, 2013). However, we have observed a specific effect of stress-induced cortisol response on retroactive interference (i.e.…”
Section: Discussioncontrasting
confidence: 97%
“…Similarly, these glucocorticoid regulation characteristics might help as well explaining why the High CORT line did not show deleterious performance in the spatial task despite the fact that they were tested during early aging. This is particularly relevant given the substantial evidence in rodents and humans implicating midlife stress (Borcel et al, 2008; Sandi and Touyarot, 2006) and cumulative exposure to high glucocorticoid levels in age-related cognitive impairments (Bodnoff et al, 1995; Buechel et al, 2014; Landfield et al, 1981; Lupien et al, 1998; Lupien and McEwen, 1997; Wheelan et al, 2018; Yau et al, 2015). It was also shown, in various species, that aged individuals are impaired in spatial reversal learning (Eppinger et al, 2011; Lai et al, 1995; Mongillo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been previously suggested that changes to the functional gating of limbic information by local PVN projections may explain age-related changes to the HPA axis (Herman et al, 2002). Stress reactivity and active coping in response to aversive experiences has previously been shown to reduce with age in mice (Oh et al, 2018) and extend beyond mice to rat and human studies (Brugnera et al, 2017;Buechel et al, 2014). There is some variability in findings possibly due to a lack of standardisation across studies including the nature and intensity of the stressor (Novais et al, 2017;Segar et al, 2009).…”
Section: Aged Mice Exhibit Emotional Bluntingmentioning
confidence: 99%